MOBILE BANKING AS AN EMERGING TREND IN COMMERCE - Sneha A.,; Patil, Hema (International Journal of Research -GRANTHAALAYAH, 2025)
Mobile banking has undergone rapid changes, and with that, these changes have transformed the scenery of modern commerce, which stands as a key drive for digital financial services. This review paper will highlight the fast-growing influence of mobile banking on commerce, emphasizing its role in accessibility, convenience, and financial inclusion. This paper further discusses key opportunities fostered through mobile banking that include the growth of digital transactions, support for small-scale business owners, and furthering the acceleration of cashless economy ventures. It also discusses major challenges such as cybersecurity threats, regulatory complexities, technological inconsistencies, and trust deficits from consumer ends. Using the latest studies, industry reports, and worldwide trends, the paper also attempts to give a detailed account of how mobile banking is affecting new commercial activities while grappling with operational and strategic challenges. The findings are anticipated to furnish useful information to policymakers and the financial sector on how to establish and promote mobile banking for sustainable growth in the emerging digital economy.